Unified analysis for tailorable multi-scale fiber reinforced cementitious composites in tension. (1st April 2023) - Zhou, Peizhao; Feng, Peng
Abstract: Fibers applied to reinforce the cementitious matrix exhibit a wide range of scales, from distributed carbon nanomaterials, chopped short fibers to continuous fibrous reinforcements. When a cementitious matrix is jointly toughened by reinforcing fibers at multiple scales, Multi-Scale Fiber Reinforced Cementitious Composite (MSFRC) tailored built on the micromechanics-based approach and bond-slip mechanism is proposed in this study. The composite actions of MSFRC, namely, tension stiffening, ductility enhancing and synergetic effects, are explained within a universal perspective. In addition, a 1-D numerical model using spring elements is developed to simulate the tensile behavior of MSFRC based on the crack band theory, fiber-bridging model and Monte Carlo simulation. The scales, types and contents of reinforcing fibers, interface behavior and stochastic nature can be considered in the model. Finally, it is found that the predicted mechanical response and crack evolution process match well with the experimental results obtained from literatures. Highlights: The concept of Multi-Scale Fiber Reinforced Cementitious Composite is presented to achieve the comprehensive utilization of materials. A model built on the bond-slip behavior and micromechanical-based approach for MSFRC is proposed and developed. The model is proved to be of wide suitability for different materials. The composite actions of reinforcing fibers at different scales have a complex effect on the tensile property and multiple-cracking behavior.